2018
DOI: 10.1159/000490415
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of the New Edition of TNM Classification of Head and Neck Squamous Cell Carcinoma

Abstract: The TNM classification is a worldwide standard staging system used to define the extent of cancer and is a major prognostic factor in predicting the outcome of patients. The TNM Classification of Malignant Tumours, 8th edition, has been used since January 1, 2018. In the area of head and neck cancer major modifications were produced: important updated T and N modification for oral cavity and nasopharyngeal cancer, the introduction of clinical and pathological stages for neck disease, and a new HPV-16-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The following three models were used to predict OS and disease-free survival (DFS), defined as the period from the first diagnosis to death due to HNSCC: a conventional clinical model, a pre-treatment PET/CT model, and a post-treatment PET/CT model. The conventional clinical model contained several pre-treatment clinical characteristics that have been linked to the survival of HNSCC patients [ 35 ]: body mass index, age, T stage, N stage, stage according to the 7 th edition of the American Joint Committee on Cancer (AJCC) guidelines, tumor location, histology grade, and smoking history. The model was optimized in a stepwise manner based on the Akaike information criterion, after which time-dependent variables were excluded by applying an assumption of proportional hazards.…”
Section: Methodsmentioning
confidence: 99%
“…The following three models were used to predict OS and disease-free survival (DFS), defined as the period from the first diagnosis to death due to HNSCC: a conventional clinical model, a pre-treatment PET/CT model, and a post-treatment PET/CT model. The conventional clinical model contained several pre-treatment clinical characteristics that have been linked to the survival of HNSCC patients [ 35 ]: body mass index, age, T stage, N stage, stage according to the 7 th edition of the American Joint Committee on Cancer (AJCC) guidelines, tumor location, histology grade, and smoking history. The model was optimized in a stepwise manner based on the Akaike information criterion, after which time-dependent variables were excluded by applying an assumption of proportional hazards.…”
Section: Methodsmentioning
confidence: 99%
“…HPV-related oral cancers, especially oropharyngeal cancers, differ from other cause-related cancers as HPV-related cancers have been seen in young, non-or former tobacco users, nonalcoholic patients, and also patients with small T tumors but with nodal involvement (fortunately, their prognosis is more satisfactory than non-related HPV tumors). In addition, HPV-related tumors are well-defined borderline, more exophytic with smaller sizes and lymph node metastasis with dominant cystic features [19]. To prevent HPV-related oral cancers, vaccination against HPV should be performed to decrease the incidence of oropharyngeal SCC [31], whereas Owosho et al [31] reported that HPV-related oropharyngeal cancer reached its highest rate in the year 2006 and has since started to decline but not at a statistically significant rate.…”
Section: Preventive Awareness and Control Care For Oral Cancersmentioning
confidence: 99%
“…In body regions wherein cancer occurs, the classifications, severity, and level determination systems differ. The most popular system evaluating cancer type and severity is the TNM system according to two recent American Joint Committee on Cancer (AJCC) editions, the seventh and eighth [13,19], used the world over due to its simplicity and friendly aspect [3]. The eighth edition has been in use since January, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck cancer (HNC) has a mortality rate of 40–50% and is detected in 600,000 cases annually worldwide, accounting for ~3.8% of global cancer cases and ~3.6% of all cancer-associated mortality (1,2). The American Joint Committee on Cancer staging system for HNC demands an integrated assessment of the patient, primarily including the primary tumor (T), lymph node metastasis (N) and distant metastasis (3). Traditionally, prognosis has been associated with tumor stage (4,5).…”
Section: Introductionmentioning
confidence: 99%